PENGARUH KEPEMIMPINAN, DISIPLIN, DAN KOMPETENSI TERHADAP PRODUKTIVITAS KERJA GURU DENGAN LOYALITAS SEBAGAI VARIABEL MEDIASI PADA SMP NEGERI 4 SURAKARTA - Ernawati, Sri Sugiyarti, Alwi Suddin & (Universitas Slamet Riyadi, 2016)
A success from school originally based on the leadership, discipline, and competency from headmaster and teachers in order to improve the productivity through high loyalty. In practice there are some problems including headmaster leadership, discipline, competency and loyalty that influence to teacher works. There are some teachers who have the high level of discipline, competency, and loyalty will produce the high productivity and the contrary. In this research, the sample is 53 people of populations of teacher in SMP N 4 Surakarta. Form instrument test shows that all variables that use in this research are valid and reliable. The classis assumptions also shows that all the variables in this research are allowed to process for next level. From test result shows that leadership, discipline, and competency are parcially influencing work prodctiviy withsignificant result and loyalty as mediation variable can influence all variable (leadership, discipline, and competency). Keywords: leadership, discipline, competency, loyalty, work productivity